Implementation of FinTech technology in Islamic banking: challenges and opportunities at Maybank Wakaf Siku / Abdul Muhyi Al Haq Halim - Halim, Abdul Muhyi Al Haq (2024)
This study aims to explore the issue of customer acceptance of FinTech technology in the context of Islamic banking and challenges related to the implementation of FinTech technology in Islamic banking at Maybank Wakaf Siku. The background of this study starts from the challenges faced by Islamic banking institutions in adapting to the rapidly developing financial technology, while ensuring compliance with Shariah principles. The main objective of this study is to investigate customer perceptions, barriers to adoption of FinTech-enabled banking services, identify challenges and opportunities offered by the integration of FinTech in the Islamic banking domain, as well as propose appropriate strategies to overcome these challenges and take advantage of the opportunities available. This qualitative study involves in-depth interviews with 5 respondents who are Maybank Wakaf Siku customers. The findings of this study show some key challenges such as security concerns and Shariah compliance, but there are also great opportunities to improve customer satisfaction and trust through more efficient use of FinTech. Through this study, it is hoped to contribute in strengthening the integration of FinTech in Islamic banking by complying with Shariah principles.